2000
DOI: 10.1038/sj.bmt.1702096
|View full text |Cite
|
Sign up to set email alerts
|

Purging in BCR-ABL-positive acute lymphoblastic leukemia using immunomagnetic beads: comparison of residual leukemia and purging efficiency in bone marrow vs peripheral blood stem cells by semiquantitative polymerase chain reaction

Abstract: Summary:Twenty autologous bone marrow (BM) and 25 peripheral blood stem cell (PBSC) grafts were collected from a total of 40 consecutive patients with BCR-ABL + acute lymphoblastic leukemia (ALL) in first (n = 37) or second (n = 3) complete morphological remission and subsequently purged with a cocktail of anti-CD19, -CD10, AB4 MoAbs and immunomagnetic beads (IMB). Residual BCR-ABL-positive cells before purging were detected in 19 of 20 BM grafts at a median of 4 (range 0-6) logs and in 17 of 25 evaluable PBSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…BM purging procedures have been disappointing. 41,49 Since the GOELAL02 study was conducted between 1994 and 1998, bone marrow was mostly used as the source of hematopoietic stem cells, and the benefit of using peripheral blood stem cells in terms of rapid engraftment 50 and lower leukemic contamination 51 could not be properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…BM purging procedures have been disappointing. 41,49 Since the GOELAL02 study was conducted between 1994 and 1998, bone marrow was mostly used as the source of hematopoietic stem cells, and the benefit of using peripheral blood stem cells in terms of rapid engraftment 50 and lower leukemic contamination 51 could not be properly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy of the pCRKL detectability in myeloid compared with lymphoblastic Ph+ leukemia is reminiscent of the fact that in ALL PCR-based detection of BCR-ABL transcripts is preferably performed in the bone marrow (BM), whereas quantification of BCR-ABL by RT-PCR reveals comparable results in BM and PB of CML patients. 12,16 We therefore hypothesize that low pCRKL levels in the PB of lyBC/Ph+ ALL patients might rather reflect differential compartmentalization of the leukemic clone than indicating BCR-ABL dependency of the disease in general. However, serial and parallel BM/PB analysis would be needed to prove this.…”
Section: Patients' Baseline Characteristicsmentioning
confidence: 99%
“…11,23,24 Arico et al 11 found no advantage for autologous BMT in first CR for children with Ph+ ALL compared with conventional chemotherapy (RR for relapse ¼ 1.1). Only 6/ 25 (24%) children who had autologous SCT in first CR survived the transplant and continued to be in CR (with no further complication like a secondary neoplasm) 2 years after transplant.…”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 99%
“…25 It has already been demonstrated that most if not all patients with Ph+ ALL who are considered as being in CR still have minimal residual disease (MRD), proven by cytogenetic or polymerase chain reaction (PCR) for Bcr-Abl. 23,26 Furthermore, reappearance of a positive PCR for BcrAbl after the patient has already achieved molecular remission predicts clinical relapse in a few months in at least 40% of the patients. 27,28 Therefore, the role of pretransplant stem cell purging has been investigated, aiming to prolong DFS and reduce relapse rate by sending the patient to transplant with the minimum disease as possible.…”
Section: Autologous Stem Cell Transplantationmentioning
confidence: 99%